2019
DOI: 10.29333/iejme/5721
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Materials Based on Realistic Mathematics Education Approach to Improve Students’ Mathematical Problem Solving Ability and Self-Efficacy

Abstract: This study aims to analyze the effectiveness of learning materials based on realistic mathematics education approach, as well as improving mathematical problem solving ability and student selfefficacy. Learning materials that developed were lesson plan, student book, student worksheet, mathematical problem solving ability test and self-efficacy questionnaire. This research is a development research by using the development model of Thiagarajan et al. (1974). Learning materials that have met valid criteria acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 14 publications
(16 reference statements)
0
43
0
10
Order By: Relevance
“…Many researchers, especially in Indonesia, researched the influence of the CORE model, as well as a realistic mathematical approach to students' mathematical problem-solving abilities. Their results show that there is an increase in students' mathematical problem-solving abilities after learning with the CORE model (Purwati, Rochmad, & Wuryanto, 2018;Wijayanti et al, 2017), and the achievement and improvement of mathematical problem-solving abilities of students who study through RME approach are better than students who learn using conventional approach (Ulandari, Amry, & Saragih, 2019;Huda, Florentinus, & Nugroho, 2020;Chong, Shahrill, & Li, 2019). These previous studies analyzed the effect of the CORE model as well as a realistic mathematical approach to problem-solving abilities, but the implementation was separated.…”
mentioning
confidence: 99%
“…Many researchers, especially in Indonesia, researched the influence of the CORE model, as well as a realistic mathematical approach to students' mathematical problem-solving abilities. Their results show that there is an increase in students' mathematical problem-solving abilities after learning with the CORE model (Purwati, Rochmad, & Wuryanto, 2018;Wijayanti et al, 2017), and the achievement and improvement of mathematical problem-solving abilities of students who study through RME approach are better than students who learn using conventional approach (Ulandari, Amry, & Saragih, 2019;Huda, Florentinus, & Nugroho, 2020;Chong, Shahrill, & Li, 2019). These previous studies analyzed the effect of the CORE model as well as a realistic mathematical approach to problem-solving abilities, but the implementation was separated.…”
mentioning
confidence: 99%
“…A systematic approach involves the implementation of a number of principles. As a fundamental principle, we singled out the principle of openness, continuity, consistency and systematicity, which "is due to objectively existing stages of cognition, the interconnection of the sensual and logical, rational and irrational, conscious and unconscious" [9,10,12,13]. The transition of knowledge from a simple step to a more complex one is a natural development process, the violation of which leads to unconscious actions and superficial knowledge and, therefore, inhibition of the development process.…”
Section: Methodsmentioning
confidence: 99%
“…Their research showed that the mathematical understanding of students taught using learning-based context was higher than those taught using the conventional method. Furthermore, Simamora, et al (2018) and Ulandari, et al (2019) used Batak context to improve students' mathematical problem solving abilities and self-efficacy. Simamora integrated the context in their learning strategy.…”
Section: Researcher (R)mentioning
confidence: 99%